Analisis SWOT Dalam Strategi Pemasaran Produk Tabungan BTN Batara iB Pada Bank BTN Syariah - Aditya Tri Purmianti; Rizal Fahlevi (LPPM Universitas Islam 45, 2022)
With increasingly advanced developments, of course it will cause intense business competition between companies. The emergence of a successful product in the market will be followed by competitors, so there needs to be an increase in the company's marketing strategy and SWOT analysis in order to remain in the market, find customers, maximize profits and of course achieve the company's vision and mission. The purpose of this research is to see how the SWOT analysis and marketing strategy of BTN Batara iB savings products at Bank BTN Syariah Bekasi Branch. The method used is a qualitative method. From the results of the SWOT analysis, it shows that Bank BTN Syariah KC Bekasi identifies internal and external factors. Thus the results of the identification of these internal factors resulted in 6 strengths and 2 weaknesses. Meanwhile, the results of the identification of the external factors resulted in 3 opportunities and 3 threats. The formulation of alternative marketing strategies for the BTN Batara iB savings product at Bank BTN Syariah KC Bekasi which is generated from the SWOT matrix is ​​by using the alternative formulation of the S-O strategy (strengths - opportunities). This SO strategy obtains three alternative strategies, namely: (1) Developing products in accordance with market demand, (2) Establishing better relationships with agencies, and (3) Improving service quality and providing quick responses to customers.